Increased Plasma Levels of the Co-stimulatory Proteins CDCP1 and SLAMF1 in Patients With Autoimmune Endocrine Diseases - Magnusson, Louise; Espes, Daniel; Casas, Rosaura; Carlsson, Per-Ola (Frontiers in Immunology, 2020)
Despite that autoimmune diseases share similar immunogenetic mechanisms, studies comparing the protein composition in peripheral blood from patients with autoimmune endocrine diseases are limited. In this study, we applied proximity extension assay to measure proteins related to signaling and interactions within the immune system in peripheral blood from patients with new-onset (N-T1D) and long-standing (L-T1D) type 1 diabetes, Hashimoto’s thyroiditis (HT), Graves’ disease (GD) and autoimmune Addison’s disease in addition to healthy controls (HC). Proteins in plasma and supernatants from cultured PBMC were measured by using a 92-plex Olink® INFLAMMATION panel. Soluble CDCP1 was more abundant in plasma from patients with N-T1D, L-T1D, HT and GD than in HC. The L-T1D and HT groups had elevated plasma levels of SLAMF1 compared with HC. Patients and HC could not be distinguished by their protein composition in PBMC supernatants. The high-throughput multiplex technology enabled us to detect two low-abundant proteins that have been gradually connected to autoimmune diseases. Our study provides novel associations between CDCP1, SLAMF1 and autoimmune endocrine diseases, which might reflect a higher degree of inflammation and lymphocyte activation.